Examining stressors’ influence on job satisfaction among engineering college faculty: a cross-sectional study - V., Krishnamoorthy; Karthikeyan, Parthasarathy; J., Rajini; V., Anandavel; Anandhan, Hariharasudan (Institute of Advanced Engineering and Science, 2025)
This study explores the various dimensions of stress experienced by engineering college teachers and their impact on job satisfaction. The research specifically examines the relationship between stress factors and job satisfaction among faculty members in engineering colleges in the western region of Tamil Nadu. A cross-sectional research design was used in this study. Data were collected using a structured questionnaire from 210 faculty members between June and December 2023, employing a convenient sampling method. The questionnaire comprised three sections: demographic details, stress dimensions, and job satisfaction variables, which were adapted from previous studies. Reliability testing ensured data consistency and factor analysis identified core stress dimensions. Multiple regression analysis was applied to assess the influence of stress dimensions on job satisfaction, while correlation analysis examined relationships between the variables. The data were analyzed using SPSS version 20. Key findings revealed that organizational climate, role conflict, professional and personal growth, and role ambiguity significantly influence job satisfaction. However, role overload did not show a notable impact. A strong correlation between professional growth and job satisfaction was observed, highlighting a critical area for targeted interventions. These insights provide valuable guidance for policymakers in academic institutions to develop effective strategies to mitigate faculty stress and enhance job satisfaction within the academic environment.